Familial mesothelioma: an understatement? - Bianchi, Claudio; Bianchi, Tommaso (La Medicina del Lavoro, 2016)
Sir,The development of malignant mesothelioma is generally the consequence of a previous exposure to asbestos. In some large mesothelioma series, nearly 100% of the cases were attributable to asbestos on the basis of the occupational data, coupled with the evaluation of asbestos exposure markers (pleural plaques, lung asbestos bodies) (4). A small percentage of subjects exposed to asbestos develop mesothelioma. This fact has been interpreted as indicating that asbestos exposure is a necessary, but not a sufficient condition (3,7). In the genesis of asbestos-related mesothelioma, the role of other factors (co-factors) is needed. These co-factors remain to be identified.[...]